2021
DOI: 10.1039/d1sc03770f
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting molecular adsorption: unconventional uptake of polymer chains from solution into sub-nanoporous media

Abstract: Self-entangled large polymeric coils in solution can go into sub-nanometer pores by spontaneous uncoiling, which has been considered unfavorable in conventional molecular adsorption models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 82 publications
(120 reference statements)
1
53
0
Order By: Relevance
“…The adsorption isotherm for PEG (M w = 2 kg/mol, hereafter referred to as PEG 2k) showed significant adsorption for both MOFs. 4 The maximum amount of adsorbed PEG 2k on these MOFs was comparable to their ideal capacity, indicating that spontaneous PEG insertion occurred simultaneously with a gradual replacement of pre-existing solvent molecules inside the MOFs. Thus, the polymer adsorption behavior showed an intriguingly high degree of solvent dependence.…”
Section: Adsorption Of Polymers On Mofs From the Solution Phasementioning
confidence: 85%
See 2 more Smart Citations
“…The adsorption isotherm for PEG (M w = 2 kg/mol, hereafter referred to as PEG 2k) showed significant adsorption for both MOFs. 4 The maximum amount of adsorbed PEG 2k on these MOFs was comparable to their ideal capacity, indicating that spontaneous PEG insertion occurred simultaneously with a gradual replacement of pre-existing solvent molecules inside the MOFs. Thus, the polymer adsorption behavior showed an intriguingly high degree of solvent dependence.…”
Section: Adsorption Of Polymers On Mofs From the Solution Phasementioning
confidence: 85%
“…Large polymers can enter and diffuse from MOF nanochannels by uncoiling themselves although they would otherwise adopt selfentangled globular conformations with hydrodynamic sizes larger than MOF pore apertures (Figure 1). 4 In this Account, we demonstrate the potential of MOFs as versatile media for polymer adsorption and recognition. Introducing polymers into the regular and well-defined MOF structure addresses the challenge of polymer separation.…”
Section: ■ Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…PEGs were used to explore the thermodynamics and kinetics of polymer insertion, which revealed an enthalpy-driven mechanism coupled with a dynamic insertion/rejection process at the solution/MOF interface. Isothermal adsorption study indicated a unique solvent dependency of PEG insertion, which is explained by PEG-MOF affinity, MOF-solvent affinity, and the solvation effect [ 131 ].…”
Section: Applications Of Zn-based Mofs For Gases Adsorption Imaging and Sensorsmentioning
confidence: 99%
“… ( a ) Zn–TDPAT emission spectra (kex at lower wavelength) at varied concentration levels and ( b ) various thermal values [ 131 ]. Reprinted with the permission of Ref.…”
Section: Figurementioning
confidence: 99%